(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing encompasses a wide range of technologies, including virtualization, distributed computing, networking, software, and online services. Customers, data centres, and distributed servers are all part of a cloud architecture.. On-demand services and low TCO are just a few of the features it offers, in addition to excellent uptime and fault tolerance. Developing a load balancing algorithm is the focus of these concerns. It is possible to have a lot or a little of each form of stress on the system. Dispersed systems can be more efficient if the burden is distributed among the system’s nodes rather than concentrated on a few nodes that are overworked while others remain idle or perform very little work. Load balancing ensures that all system and network nodes are doing roughly the same amount of work at any one time. Techniques that are either sender initiated, receiver initiated, symmetric, static or dynamic, centralised or distributed are all feasible. Depending on the time of day, up to 80 of workstations are idle, making them a valuable resource. The idle time and compute resources of a processor can be used to reduce the cost of processing. Explain the concept of load balancing, different types of load balancing algorithms, and the various policies that can be used in load balancing algorithms in general, as well as provide an overview of various distributed load balancing algorithms that can be used in cloud environments. Our goal is to